Bile acids as global regulators of hepatic nutrient metabolism - Hylemon, Phillip B. (Liver Res, 2017)
Bile acids (BA) are synthesized from cholesterol in the liver. They are essential for promotion of the absorption of lipids, cholesterol, and lipid-soluble vitamins from the intestines. BAs are hormones that regulate nutrient metabolism by activating nuclear receptors (farnesoid X receptor (FXR), pregnane X receptor, vitamin D) and G protein-coupled receptors (e.g., TGR5, sphingosine-1-phosphate receptor 2 (S1PR2)) in the liver and intestines. In the liver, S1PR2 activation by conjugated BAs activates the extracellular signal-regulated kinase 1/2 and AKT signaling pathways, and nuclear sphingosine kinase 2. The latter produces sphingosine-1-phosphate (S1P), an inhibitor of histone deacetylases 1/2, which allows for the differential up-regulation of expression of genes involved in the metabolism of sterols and lipids. We discuss here the emerging concepts of the interactions of BAs, FXR, insulin, S1P signaling and nutrient metabolism.